Lack of the Transient Receptor Potential Vanilloid 1 Shifts Cannabinoid-Dependent Excitatory Synaptic Plasticity in the Dentate Gyrus of the Mouse Brain Hippocampus - Jon Egaña-Huguet; Jon Egaña-Huguet; Miquel Saumell-Esnaola; Miquel Saumell-Esnaola; Svein Achicallende; Svein Achicallende; Edgar Soria-Gomez; Edgar Soria-Gomez; Edgar Soria-Gomez; Itziar Bonilla-Del Río; Itziar Bonilla-Del Río; Gontzal García del Caño; et al. (Frontiers Media S.A., 2021)
The transient receptor potential vanilloid 1 (TRPV1) participates in synaptic functions in the brain. In the dentate gyrus, post-synaptic TRPV1 in the granule cell (GC) dendritic spines mediates a type of long-term depression (LTD) of the excitatory medial perforant path (MPP) synapses independent of pre-synaptic cannabinoid CB1 receptors. As CB1 receptors also mediate LTD at these synapses, both CB1 and TRPV1 might be influencing the activity of each other acting from opposite synaptic sites. We tested this hypothesis in the MPP-GC synapses of mice lacking TRPV1 (TRPV1-/-). Unlike wild-type (WT) mice, low-frequency stimulation (10 min at 10 Hz) of TRPV1-/- MPP fibers elicited a form of long-term potentiation (LTP) that was dependent on (1) CB1 receptors, (2) the endocannabinoid 2-arachidonoylglycerol (2-AG), (3) rearrangement of actin filaments, and (4) nitric oxide signaling. These functional changes were associated with an increase in the maximum binding efficacy of guanosine-5'-O-(3-[35S]thiotriphosphate) ([35S]GTPγS) stimulated by the CB1 receptor agonist CP 55,940, and a significant decrease in receptor basal activation in the TRPV1-/- hippocampus. Finally, TRPV1-/- hippocampal synaptosomes showed an augmented level of the guanine nucleotide-binding (G) Gαi1, Gαi2, and Gαi3 protein alpha subunits. Altogether, the lack of TRPV1 modifies CB1 receptor signaling in the dentate gyrus and causes the shift from CB1 receptor-mediated LTD to LTP at the MPP-GC synapses.